Consumer Attitudes Toward Advertisement and Brand, Based on the Number of Endorsers and Product Involvement: An Experimental Study - Tanti Handriana; Wahyu Rahman Wisandiko (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Utilizing endorsers in the advertising industry to promote products is currently on the rise, and employing celebrities as the endorsers is still the marketers’ favorite method. This study aims to analyze the influence of the number of endorsers and the product’s involvement on the consumers’ attitude towards the advertisement and the brand. The research’s approach used a 2x2 factorial experimental design. A total of 120 undergraduate students, who were further divided into 4 groups, were selected as the respondents of this study. The results show the differences in consumer attitudes towards advertisements and the brand, based on the number of endorsers and the product’s involvement. The study also reveals that if there is low involvement with the product, multiple celebrity endorsements will generate a better consumers’ attitude towards it than a single celebrity endorsement. Multiple celebrity endorsements will also generate a better attitude among the consumers towards the brand than a single celebrity endorsement will produce.